2015
DOI: 10.1080/02772248.2015.1101112
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone screening of human breast milk from the Naples area

Abstract: The mycotoxin zearalenone exhibits estrogenic and anabolic properties in several animal species, humans included. Food contamination by zearalenone is caused either by direct contamination of grains, fruits and their based-products or by "carry-over" of mycotoxins in animal tissues, milk and eggs after intake of contaminated feedstuff. Now, a survey on zearalenone contamination in breast milk of healthy primiparous women living in the Naples countryside was conducted. From 47 healthy primiparous women, breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
(7 reference statements)
2
18
2
Order By: Relevance
“…QuEChERS methodology was satisfactorily performed for the analysis of several mycotoxins in human breast milk including DON, 3-ADON, NIV, FUX-N, DAS, NEO, T-2, HT-2, ZON and metabolites, OTA, STG, ENs, BEA, and AFs [ 110 ]. Direct IAC was used for ZON, AFM1, and AFM2 extraction from cow [ 22 ], human [ 111 ] and donkey [ 23 ] breast milk samples. DON, DOM-1, T-2 and HT-2 were extracted from bile and serum samples from pig and chicken by LLE using MeOH/H 2 O and EtOAc [ 112 , 113 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…QuEChERS methodology was satisfactorily performed for the analysis of several mycotoxins in human breast milk including DON, 3-ADON, NIV, FUX-N, DAS, NEO, T-2, HT-2, ZON and metabolites, OTA, STG, ENs, BEA, and AFs [ 110 ]. Direct IAC was used for ZON, AFM1, and AFM2 extraction from cow [ 22 ], human [ 111 ] and donkey [ 23 ] breast milk samples. DON, DOM-1, T-2 and HT-2 were extracted from bile and serum samples from pig and chicken by LLE using MeOH/H 2 O and EtOAc [ 112 , 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…For human biomonitoring easily accessible biological matrices such as urine or blood were used, with urine being preferred for several reasons including non-invasive sampling and higher acceptance by study participants. Consequently, biomonitoring studies have been frequently performed almost worldwide ( Figure 3 ), including Nigeria [ 70 ], Bangladesh [ 58 , 69 , 85 , 86 , 88 , 96 ], Haiti [ 69 ], Turkey [ 64 , 106 ], Belgium [ 73 , 74 , 105 ], Portugal [ 60 , 61 , 89 ], Spain [ 36 , 61 , 93 ], Germany [ 35 , 62 , 64 , 68 , 69 , 86 , 87 ], Italy [ 77 , 111 ], Austria [ 72 ], Czech Republic [ 38 , 43 ], Tunisia [ 41 ], Brazil [ 40 , 109 ], Chile [ 44 ], Cameroon [ 141 ], Egypt [ 50 ], Pakistan [ 37 ], Iran [ 107 ], and China [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OTA is carcinogenic in rodents and nephrotoxic in many mammal species; it has been also classified by IARC as possibly carcinogenic to humans and its presence in breast milk has been widely outlined [ 5 ]. The biomonitoring of ZEA is also important due to its toxic effects mainly on the reproductive system [ 6 ]; moreover, ZEA contamination was previously described in breast milk in Italy [ 7 ]. Consumers can be at risk of mycotoxins exposure both directly, by consuming contaminated grains, seeds, and dried fruits, or indirectly, by consuming contaminated animal source food (e.g., milk) derived from animals exposed to these contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that most reports overestimate infant's exposure to mycotoxins. For example, Massart et al (2016) reported a mean ZEN concentration of 1130 ng/L, which may be the result of using less specific analytical approaches. Here, cross-reactivity reactions (ELISA) or interfering peaks (LC-FD) may be interpreted as positive signals.…”
Section: Interval Days Postpartummentioning
confidence: 99%